Rice SCAMP1 defines clathrin-coated, trans-Golgi-located tubular-vesicular structures as an early endosome in tobacco BY-2 cells - Lam, Sheung Kwan; Hillmer, Stefan; Robinson, David G. (The plant cell, 2007)
We recently identified multivesicular bodies (MVBs) as prevacuolar compartments (PVCs) in the secretory and endocytic pathways to the lytic vacuole in tobacco (Nicotiana tabacum) BY-2 cells. Secretory carrier membrane proteins (SCAMPs) are post-Golgi, integral membrane proteins mediating endocytosis in animal cells. To define the endocytic pathway in plants, we cloned the rice (Oryza sativa) homolog of animal SCAMP1 and generated transgenic tobacco BY-2 cells expressing yellow fluorescent protein (YFP)-SCAMP1 or SCAMP1-YFP fusions. Confocal immunofluorescence and immunogold electron microscopy studies demonstrated that YFP-SCAMP1 fusions and native SCAMP1 localize to the plasma membrane and mobile structures in the cytoplasm of transgenic BY-2 cells. Drug treatments and confocal immunofluorescence studies demonstrated that the punctate cytosolic organelles labeled by YFP-SCAMP1 or SCAMP1 were distinct from the Golgi apparatus and PVCs. SCAMP1-labeled organelles may represent an early endosome because the internalized endocytic markers FM4-64 and AM4-64 reached these organelles before PVCs. In addition, wortmannin caused the redistribution of SCAMP1 from the early endosomes to PVCs, probably as a result of fusions between the two compartments. Immunogold electron microscopy with high-pressure frozen/freeze-substituted samples identified the SCAMP1-positive organelles as tubular-vesicular structures at the trans-Golgi with clathrin coats. These early endosomal compartments resemble the previously described partially coated reticulum and trans-Golgi network in plant cells.